1985
DOI: 10.1002/1097-0142(19850115)55:2<460::aid-cncr2820550229>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Diet and other risk factors for cancer of the pancreas

Abstract: The findings of a case‐control study of cancer of the pancreas, which was conducted in the Baltimore metropolitan area, are reported. Two hundred one patients with pancreatic cancer were matched on age (±5 years), race, and sex to hospital and non‐hospital controls, the latter selected by random‐digit‐dialing (RDD). All subjects were interviewed regarding diet, beverage consumption, occupational and environmental exposures, and medical and surgical history. Significantly decreased risks were associated with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
114
5
4

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(136 citation statements)
references
References 26 publications
13
114
5
4
Order By: Relevance
“…A protective effect for allergic conditions including asthma has been reported in some studies of pancreatic cancer (Mack et al, 1986;Mills et al, 1988;Jain et al, 1991;Bueno de Mesquita et al, 1992;Kalapothaki et al, 1993;Dai et al, 1995), but our results are consistent with three studies that showed little effect (Gold et al, 1985;Farrow and Davis, 1990;La Vecchia et al, 1990). Since most case-control studies of pancreatic cancer have been based primarily on interviews with next of kin, the reliability of detailed information on allergic disorders may be questionable (Gavalda et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…A protective effect for allergic conditions including asthma has been reported in some studies of pancreatic cancer (Mack et al, 1986;Mills et al, 1988;Jain et al, 1991;Bueno de Mesquita et al, 1992;Kalapothaki et al, 1993;Dai et al, 1995), but our results are consistent with three studies that showed little effect (Gold et al, 1985;Farrow and Davis, 1990;La Vecchia et al, 1990). Since most case-control studies of pancreatic cancer have been based primarily on interviews with next of kin, the reliability of detailed information on allergic disorders may be questionable (Gavalda et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…The Multiethnic Cohort Study, which has a substantial number of pancreatic cancer cases (n = 482), reported significant 45% and 68% increased risks in the highest compared with the lowest intake of red and processed meat, respectively (26). Meat-cooking methods and pancreatic cancer risk has been evaluated in one cohort study that reported no associations (30) and eight case-control studies (2,3,8,9,12,13,19,22), five of which showed greater pancreatic cancer risk for fried or grilled/barbecued meats, with odds ratios ranging from 2.2 to 16.7 (3,8,9,12,22). Two recent pancreatic cancer case-control studies have employed a meat-cooking module and mutagen database similar to that used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The association between meat intake and pancreatic cancer has been examined in both case control and cohort (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) studies with positive (2-7, 9-12, 22-27), inverse (13)(14)(15)28), and null (4, 5, 8, 14-21, 29, 32) associations reported for both study designs. The inconsistent results among case-control studies may partly be due to retrospective ascertainment of diet, which, given the rapid fatality of pancreatic cancer, may be fraught with biases, such as recall and proxy, and reverse causation.…”
Section: Introductionmentioning
confidence: 99%
“…27,46-48 Further investigations are necessary to identify any causal relationship between the pathogenesis of diabetes and pancreatic cancer. Also, some case-control studies [49][50][51][52][53][54][55][56][57] and cohort studies [58][59][60][61][62] have found an association between the duration of diabetes and pancreatic cancer. Everhart and Wright 27 reported in their metaanalysis of 6 case-control and 5 cohort studies that diabetes of at least 5 years resulted in an RR of 2.0 (95% CI 5 1.2-3.2).…”
Section: Discussionmentioning
confidence: 99%